Using Animated Videos in Science Learning on Learning Outcomes of Primary School Students: a Systematic Literature Review - Maya Angelika; Junaidi junaidi; Yasinta Mahendra (International Journal of Elementary Education, 2025)
This study aims to analyze the effectiveness of using animated videos in enhancing students’ learning outcomes in Science learning at the primary school level. The study is motivated by the need for instructional media that can visualize abstract scientific concepts, making them easier for students to understand. This research employs a Systematic Literature Review (SLR) approach by examining relevant scholarly articles published between 2019 and 2023 retrieved from the Google Scholar database. Out of 1,830 identified articles, eight met the inclusion criteria and were analyzed in depth using a thematic analysis approach. The findings reveal that the use of animated videos significantly improves students’ learning outcomes by presenting scientific concepts in a more concrete, engaging, and interactive manner. Furthermore, animated videos enhance students’ motivation and engagement during the learning process. The effectiveness of this medium is strongly influenced by the quality of its design, its alignment with learning objectives, and the teacher’s role in its implementation. The study concludes that animated videos serve as an innovative instructional medium that can enrich Science learning experiences and improve the quality of learning in primary education.